“PUISI POLITIK” DALAM KAMPANYE PILPRES RI 2014 - Patji, Abdul Rachman (Jurnal Masyarakat dan Budaya, 2015)
This article discusses political poetry that occurs during Indonesian’s election campaign, specially presidential campaign 2014. Both of competed parties, such as Prabowo’s side (KMP) and Jokowi’s side (KIH) peformed their own political poetry and reciprocate each other, on the contrary there are some of poetry made by society. Apart from read out, the poetry also appears in social media. The emersion of this poetry is quite enticing, although it is not an utterly new phenomena. The political poetry 2014 adds new polemic space, diversity of vision and mission and program that offered by candidate and elector. The political poetry indeed is a form of moderate media, thrifty, cultured, and have high moral standard in campaign besides using open campaign and mass support. It is just still be found some of poetry that contain mockery, agitation, shows resentment and jealousy, moreover offend president candidate personal. Keywords : political poetry, presidential election, presidential campaign